Pre-emptive analgesia with diclofenac in combination with ketamine in patients undergoing laparoscopic cholecystectomy - Soni, Vikas; Gupta , Suman; Deepak Singh Gurjar; Nancy Ekka; Verma , Gargi (Asian Journal of Medical Sciences, 2025)
Background: Laparoscopic cholecystectomy is a minimally invasive surgery which most often is associated with post-operative pain. Pre-emptive administration of ketamine and diclofenac in combination reduces post-operative pain. Aims and Objectives: In patients undergoing laparoscopic cholecystectomy, the aim of this study was to evaluate the efficacy of preemptively administered ketamine and diclofenac and their combination on post-operative pain. Materials and Methods: A total of 90 patients, with American Society of Anesthesiologists physical grading I and II, were recruited for the study. Patients were allocated randomly into the following groups: Group I was administered 100 mL isotonic saline intravenous (IV) 20 min before the induction of anesthesia and 0.15 mg/kg ketamine IV diluted in 5-mL isotonic saline before skin incision; Group II received diclofenac in the dose of 1 mg/kg diluted in 100-mL isotonic saline IV 20 min before the induction of anesthesia and 5-mL isotonic saline IV before skin incision; Group III was administered a combination of diclofenac 1 mg/kg diluted in 100-mL isotonic saline IV 20 min before the induction of anesthesia and 0.15 mg/kg ketamine diluted in 5-mL isotonic saline IV before skin incision. Time for rescue analgesia, post-operative Visual Analog Scale score, hemodynamic changes, and adverse effects were evaluated. Results: Post-operative analgesia was longer in Group III as compared to Group II and Group I at 2, 4, and 6 h (P<0.05). The mean time to receive rescue analgesia was significantly higher in Group III (6.950±0.6208) and Group II (5.633±0.7184) as compared to Group I (2.833±0.6205). Significantly higher heart rate and blood pressure were noted in Group I as compared to Group II and Group III at 2, 4, and 6 h postoperatively. Conclusion: Administration of ketamine and diclofenac preemptively in the patients undergoing laparoscopic cholecystectomy has a definitive role in providing post-operative analgesia without any adverse side effects whereas ketamine alone when given preemptively did not produce any benefit in post-operative pain relief.